On-farm trials of WorldFish Genetically Improved Rohu - Hamilton, Matthew; Yeasin, Mohammed; Alam, Md. Badrul; Ali, Md. Rayhan; Fakhruddin, Md.; Islam, Md. Mazharul; Barman, Benoy; Shikuku, Kelvin; Shelley, Colin; Rossignoli, Cristiano; Benzie, John (Sylhet Agricultural University, 2022)
Rohu Labeo rohita (Hamilton) is an economically and culturally significant aquaculture species in Bangladesh. However, until recently, genetically improved rohu strains have not been available to Bangladeshi farmers. In 2020, a multiplier population comprised of highly-ranked families from the third selected generation of the WorldFish Rohu Genetic Improvement Program (the ‘G3 multiplier’) was released to commercial hatcheries as spawn. This spawn was subsequently developed into broodstock by these hatcheries and sale of this genetically improved product commenced in 2022. To assess the performance of (i.e. estimate realised genetic gain in) the G3 multiplier population, on-farm trials were undertaken in 2021-22. One pond, in each of 19 Bangladeshi semi-commercial farms, was stocked with equal numbers of tagged fish from three treatments – the ‘G3 multiplier’, a ‘control’ strain (putatively genetically equivalent to unimproved riverine stocks) and a ‘commercial’ strain – and managed according to each farmer’s normal practices. At harvest, the G3 multiplier had the greatest mean harvest weight in each of the 19 farms and exhibited a mean realised genetic gain of 37% over the control. The growth rate of the commercial strain was similar to that of the control. The greater harvest weight exhibited by the G3-multiplier over the control and commercial strains in this study verified that the WorldFish Rohu Genetic Improvement Program has attained a rate of genetic gain comparable to that achieved in other family-based (i.e. pedigree-based) finfish programs over its first three generations.